Meeting with Mussolini : Tagore's Tours in Italy, 1925 and 1926 - Kundu, Kalyan (New Delhi Oxford Univ. Press, 2015)
This work is an evaluation of Rabindranath Tagore's much-debated tours to Italy in 1925 and 1926 at the invitation of the fascist dictator Benito Mussolini. It is based on a vast corpus of reportage available on this controversial Tagore-Mussolini episode
Include Appendix and Index
Keywords: Travel -- Italy -- Mussolini, Benito, 1883-1945